Morphology, crystallization, and thermal and mechanical properties of dynamic vulcanization EPDM/PP thermoplastic elastomer. (July 2019) - Shi, Min; Zhang, Daohai; Zhu, Jianhua; Shi, Yinping; Sun, Jing; Ji, Yubi
Dynamically vulcanized thermoplastic olefin based on polypropylene (PP)/ethylene–propylene–diene (EPDM) with different dicumyl peroxide (DCP) content was prepared by twin-screw extruder. The effect of DCP content on gel content, crystallinity, and morphological, thermal, and mechanical properties of dynamically vulcanized EPDM/PP blends with different DCP content was investigated. The scanning electron microscopy was performed to evaluate the structure, as well as to characterize the morphology formed during dynamic vulcanization. The regular cross-linked EPDM particle uniformly distributed in PP matrix when the DCP content was from 0.3% to 0.9%. The crystallization behavior analysis indicated that the cross-linked EPDM promoted the nucleation process of PP, but with increase in DCP content, the percentage of crystallinity of the dynamically vulcanized EPDM/PP blends decreased due to the PP degradation. The tensile strength and elongation at break first increase and then decrease with increase in DCP content. When the DCP content was 0.9%, the tensile strength and elongation at break of dynamically vulcanized EPDM/PP blends were the largest. The gel content of dynamically vulcanized EPDM/PP blends first increased and then decreased with increasing DCP content. When the DCP content was 1.2%, the gel content of dynamically vulcanized EPDM/PP blends was maximum. The proper content range of DCP was from 0.6% to 1.2%.